KEMAMPUAN MENYELESAIKAN SOAL CERITA MATEMATIKA - Astra Puspita Kaprinaputri (JIV-Jurnal Ilmiah Visi, 2013)
This study aims to describe the ability of Kumonâ€™s students, 7-8 years old, in solving mathematics word problems. This study done in December 2012 used cumulative approach with survey method. The respondents were the students of Kuman Course in North Jakarta. The data collected by distributing the questions to the respondents were analyzed applying simple statistic technique. Findings show that 86%of the respondents belong to high category while 14% belong to medium category. and no students belongs to low category. The implication of this study is Kumon students have the ability to solve mathematics word problem, but they still have to do more exercises in solving mathematics word problems continually. Besides, the Kumon Course should use media in the teaching of mathematics word problems.